2014
DOI: 10.1007/s00170-014-6364-8
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir blind riveting of carbon fiber-reinforced polymer composite and aluminum alloy sheets

Abstract: A friction stir blind riveting (FSBR) process is used to fabricate joints of carbon fiber-reinforced polymer composite (CFRP) and aluminum alloy AA6111 sheets in a lap shear configuration. Given the 9,000 rpm spindle speed upper limit of conventional computer numerically controlled machines, the maximum feed rate for FSBR joining CFRP to itself is found to be 120 mm min −1 above which quality issues such as cracking of the CFRP sheet predominate. However, the maximum feed rate during dissimilar joining of CFRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Prior studies revealed that CFRP in FSBR joints failed near the rivet hole, suggesting that the stir-affected zone possessed distinct mechanical properties [3]. As the strength and stiffness of fiber-reinforced composites is intimately related to fiber volume, porosity and fiber orientation, we explored these parameters near the rivet hole in the stir-affected zone and compared these values to the bulk material.…”
Section: Microstructural Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies revealed that CFRP in FSBR joints failed near the rivet hole, suggesting that the stir-affected zone possessed distinct mechanical properties [3]. As the strength and stiffness of fiber-reinforced composites is intimately related to fiber volume, porosity and fiber orientation, we explored these parameters near the rivet hole in the stir-affected zone and compared these values to the bulk material.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…The reconstructed images captured at 0, 22 and 44 MPa compressive loads were correlated using commercial V-DIC software (Vic-Volume v1.09, Correlated Solutions Inc.) to calculate the full-field displacement and strain tensors using subset size of [35 voxels] 3 and subset spacing of 15 voxels (equivalent to [47 μm] 3 and 20 μm, respectively). Fibers, pores and other microstructural features with pseudo-random orientation, size and location provided an intrinsic high-contrast speckle pattern for displacement calculations.…”
Section: Volumetric Digital Image Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of joining methods have been used for joining CFRP-aluminum alloys, such as adhesive joining [3], friction stir joining [4], ultrasonic joining [5] and laser joining [6]. Adhesive joining is a conventional process for joining plastics, including CFRP to metals [7].…”
Section: Introductionmentioning
confidence: 99%
“…Sheet molding compounds (SMCs) have gained extensive use in the area of new-energy vehicles to realize the light-weight requirements thereof [1,2]. However, a method whereby to joint the SMC substrates to ensure adequate automotive safety becomes important as the number of joining demands increases [3].…”
Section: Introductionmentioning
confidence: 99%